Cancer screening in the United States, 2017: A review of current American Cancer Society guidelines and current issues in cancer screening - Smith, Robert A.; Andrews, Kimberly S.; Brooks, Durado; Fedewa, Stacey A.; Manassaram‐Baptiste, Deana; Saslow, Debbie; Brawley, Otis W.; Wender, Richard C. (CA: a cancer journal for clinicians, 2017)
ABSTRACT Answer questions and earn CME/CNE Each year, the American Cancer Society publishes a summary of its guidelines for early cancer detection, data and trends in cancer screening rates, and select issues related to cancer screening. In this issue of the journal, the authors summarize current American Cancer Society cancer screening guidelines, describe an update of their guideline for using human papillomavirus vaccination for cancer prevention, describe updates in US Preventive Services Task Force recommendations for breast and colorectal cancer screening, discuss interim findings from the UK Collaborative Trial on Ovarian Cancer Screening, and provide the latest data on utilization of cancer screening from the National Health Interview Survey. CA Cancer J Clin 2017;67:100–121. © 2017 American Cancer Society.